Lending Resumption After Default : Lessons from Capital Markets During the 19th Century - Sole, Juan (IMF Working Papers; Working Paper ;, 2006)
This paper mines the experience of capital markets during the 19th century to propose an alternative way of interpreting international default episodes. The standard view is that defaulting on sovereign debt entails exclusion from capital markets. Yet we have observed multiple instances of sovereign debt default in which the reaction of lenders was not the one predicted by the punishment story: in some cases, lending ceased for long periods, but in others it was not interrupted. This paper claims that the reaction of lenders after default stems from the additional knowledge about the borrower that lenders acquire during these episodes. The lending relationship is modeled in a costly state-verification environment in which governments have private information about their investment projects (good or bad). It is shown that, in the event of default, it is worthwhile for lenders to find out more about the type of project, and then interrupt lending only if the project is believed to be a bad one.